Characterization of AreABC, an RND-Type Efflux System Involved in Antimicrobial Resistance of Aliarcobacter butzleri - Ferreira, Susana (2022)
Aliarcobacter butzleri is an emergent enteropathogen for which resistance to several classes of antimicrobial agents has been described, although the underlying mechanisms have been poorly addressed. We aimed to evaluate the contribution of the resistance-nodulation-division-type (RND) efflux system, AreABC, to drug resistance in A. butzleri. A. butzleri strains were first tested against several antimicrobials with and without an efflux pump inhibitor. Then, erythromycin-resistant strains were screened for the presence of a premature stop codon in a putative transcriptional regulator of the AreABC system, areR. Lastly, antimicrobial susceptibility and ethidium bromide (EtBr) accumulation were evaluated using an areB knockout strain and a strain overexpressing the AreABC system through areR truncation. The presence of the efflux pump inhibitor resulted in increased susceptibility to most of the antimicrobials tested. A correlation between erythromycin resistance and the presence of premature stop codons in areR was observed. The truncation of areR resulted in increased expression of the AreABC system and decreased susceptibility to various antimicrobials. In contrast, areB inactivation resulted in increased susceptibility and a higher intracellular accumulation of EtBr. In conclusion, the AreABC efflux pump plays a role in the resistance of A. butzleri to multiple drugs and is regulated by a putative transcriptional repressor, areR. Our results support the importance of efflux pumps in this bacterium's resistance to major classes of antibiotics and other antimicrobials.